Comparison of the New Oral Anticoagulants and Warfarin in Patients with Atrial Fibrillation and Valvular Heart Disease: Systematic Review and Meta-Analysis - Yasmin de Souza Lima Bitar; Mansueto Gomes Neto; Jose Admirço Lima Filho; Larissa Vitória Pereira; Kethyren Santos Oliveira Travassos; Kevan M. Akrami; Leonardo Roever; Andre Rodrigues Duraes (Adis, Springer Healthcare, 2019)
Abstract Introduction New oral anticoagulants (NOACs) are approved for use in nonvalvular atrial fibrillation (AF). Objectives This study aimed to evaluate the efficacy and safety of NOACs compared with warfarin in AF and valvular heart disease (VHD). Methods We identified randomized controlled trials (RCTs) and post-hoc analyses comparing NOACs and warfarin in AF and VHD, including biological and mechanical heart valves (MHV). Through systematic review and meta-analysis, with the aid of the "Rev Man" program 5.3, the primary effectiveness endpoints were stroke and systemic embolism (SE). The primary safety outcome was major bleeding, and the secondary outcome included intracranial hemorrhage. Data were analyzed using risk ratios (RRs) and 95% confidence intervals (CIs), and heterogeneity was assessed using the I 2 statistic. Results Six RCTs were included, involving 13,850 patients with AF and VHD. NOACs significantly reduced the risk of stroke/SE (RR 0.78; 95% CI 0.66-0.91; P = 0.002) and intracranial hemorrhage (RR 0.51; 95% CI 0.33-0.79; P = 0.003) and lowered the risk of major bleeding (RR 0.77; 95% CI 0.58-1.02; P = 0.07) compared with warfarin. Conclusions The efficacy and safety of NOACs as thromboprophylaxis for AF and VHD are similar to those of warfarin.